Overlapping Properties of the Short Membrane-Active Peptide BP100 With (i) Polycationic TAT and (ii) α-helical Magainin Family Peptides - Mink, Christian; Strandberg, Erik; Wadhwani, Parvesh; Melo, Manuel N.; Reichert, Johannes; Wacker, Irene; Castanho, Miguel A. R. B.; Ulrich, Anne S. (Frontiers in Cellular and Infection Microbiology, 2021)
BP100 is a short, designer-made membrane-active peptide with multiple functionalities: antimicrobial, cell-penetrating, and fusogenic. Consisting of five lysines and 6 hydrophobic residues, BP100 was shown to bind to lipid bilayers as an amphipathic α-helix, but its mechanism of action remains unclear. With these features, BP100 embodies the characteristics of two distinctly different classes of membrane-active peptides, which have been studied in detail and where the mechanism of action is better understood. On the one hand, its amphiphilic helical structure is similar to the pore forming magainin family of antimicrobial peptides, though BP100 is much too short to span the membrane. On the other hand, its length and high charge density are reminiscent of the HIV-TAT family of cell penetrating peptides, for which inverted micelles have been postulated as translocation intermediates, amongst other mechanisms. Assays were performed to test the antimicrobial and hemolytic activity, the induced leakage and fusion of lipid vesicles, and cell uptake, and from these results the functional profile of BP100 with the other two classes of peptides were determined and compared. It is observed that the activity of BP100 resembles most closely the much longer amphipathic -helical magainin-like peptides, with high antimicrobial activity along with considerable fusogenic and hemolytic effects. In contrast, HIV-TAT shows almost no antimicrobial, fusogenic, or hemolytic effects. We conclude that the amphipathic helix of BP100 has a similar membrane-based activity as magainin-like peptides and may have a similar mechanism of action.